Systematic review of international guidelines for tracheostomy in COVID-19 patients. (September 2020) - Chiesa-Estomba, Carlos M.; Lechien, Jérome R.; Calvo-Henríquez, Christian; Fakhry, Nicolas; Karkos, Petros D.; Peer, Shazia; Sistiaga-Suarez, Jon A.; Gónzalez-García, José A.; Cammaroto, Giovanni; Mayo-Yánez, Miguel; Parente-Arias, Pablo; Saussez, Sven; et al.
Highlights: At this moment, the world lives under the SARS-CoV-2 outbreak pandemic. Tracheostomy represent an essential procedure due the increasing admission in ICU departments. Tracheostomy recommendations are needed to ensure the safety of healthcare workers. Abstract: At this moment, the world lives under the SARS-CoV-2 outbreak pandemic. As Otolaryngologists - Head & Neck Surgeons, we need to perform and participate in examinations and procedures within the head and neck region and airway that carry a particularly high risk of exposure and infection because of aerosol and droplet contamination. One of those surgical procedures in demand at this moment is tracheostomy due the increasing ICU admissions. This review of international guidelines for tracheostomy in COVID-19 infected patients, aims to summarize in a systematic way the available recommendations: indications, timing, technique and safety measures for tracheostomy, from all over the world.